HUBUNGAN ANTARA MOTIVASI BELAJAR DENGAN HASIL BELAJAR MATEMATIKA SISWA KELAS V DI SD NEGERI 3 DELOD PEKEN TABANAN - Ni Putu Anggi Dama Yanti; A.A. Ngurah Budiadnyana; Ni Nyoman Tri Wahyuni (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2026)
Mathematics learning in elementary school plays an important role in developing students’ logical thinking, systematic reasoning, and problem-solving skills. However, the mathematics learning outcomes of Grade V students at SD Negeri 3 Delod Peken Tabanan still show variation and are not yet optimal. This is indicated by the presence of students who have not achieved the Minimum Mastery Criteria (KKTP), as well as uneven levels of student learning motivation. This condition suggests a relationship between learning motivation and students’ mathematics learning outcomes. Therefore, this study aims to determine the relationship between learning motivation and mathematics learning outcomes of Grade V students at SD Negeri 3 Delod Peken Tabanan. This research employed a quantitative approach with a correlational research design. The research subjects consisted of 43 students. Data collection techniques were carried out through questionnaires to measure learning motivation and document analysis to obtain data on mathematics learning outcomes in the form of Final Semester Assessment (SAS) scores. The data were analyzed using descriptive analysis and Pearson Product Moment correlation test. The results showed that the average student learning motivation score was 69.05 (moderate category), and the average mathematics learning outcome was 77.37 (good category). There is a positive, strong, and significant relationship between learning motivation and students’ mathematics learning outcomes, with a correlation coefficient of r = 0.796 and a significance value of < 0.001 (< 0.05). Thus, H₀ is rejected and Hₐ is accepted. The coefficient of determination of 63.3% indicates that learning motivation contributes significantly to students’ mathematics learning outcomes. In conclusion, the higher the students’ learning motivation, the higher their mathematics learning outcomes.